GENERAL ASPECTS REGARDING THE AUDIT OF EUROPEAN NON-REIMBURSABLE FUNDS - BOGDAN RĂVAŞ (Annals of the University of Petrosani: Economics)
Based on the EU regulations applicable to European funds, in Romania the institutional and procedural framework regarding the coordination, management, control and audit of European funds was established, respectively management authorities, certification authorities and the audit authority for each operational program implemented in the two periods of programming carried out to date, 2007-2013 and 2014-2020.